A nostalgia colonial como técnica de best-selling literário - Giorgio de Marchis (Cadernos de Estudos Africanos)
The article analyses Miguel Sousa Tavares’ novel Equador in the light of the sensational success that the book had, mainly in Portugal. In addition to a fictional strategy of paraliterary character, the skilful recovery and banalization of the Queirosian lesson appears as one of the elements that, by offering a comfortable reading of a pleasure text (in a barthesian sense), justifies the great acceptance that this best-seller received in the Portuguese editorial market. Still, Miguel Sousa Tavares' novel, as well as other works published in Portugal in the preceding years, responds mainly to the social desire, nowadays very generalized in the mnemonic Portuguese community, of sharing a positive image of Africa’s past. From this point of view, Equador obeys, and simultaneously feeds certain social rules of rememberance and can then be considered an historical novel that functions as an aggregation factor of a community that recognizes itself while remembering and consuming the same image of the past and, simultaneously, as a generator of this same alternative image of the colonial history that contributes to filter and alter through the reconfiguration of the historical segment markers in question.